Pengaruh Brand Image Terhadap Keputusan Pembelian Produk HNI HPAI Kota Prabumulih - Aptiani, Rolisa; Kaharuddin, M. Robby (ADL ISLAMIC ECONOMIC : Jurnal Kajian Ekonomi Islam, 2024)
This study aims to determine the effect of brand image on purchasing decisions for HNI HPAI products in Prabumulih City. The method used in this research is quantitative research method using a sample of 100 respondents. Sampling using purposive sampling technique The data analysis method used in this research is simple linear regression to see how much influence Brand Image has on purchasing decisions for HNI HPAI Products in Prabumuih City. Based on the results of simple linear regression analysis that has been carried out in this study, seen from the results of the t test, it is found that tcount 2.986> ttable 1.660, so Ho can be rejected and Ha is accepted, it can be concluded that Brand Image has a positive effect on purchasing decisions for HNI HPAI Products in Prabumulih City.